ATTITUDE OF TEACHERS TO THE APPLICATION OF FITNESS GADGETS IN PHYSICAL EDUCATION LESSONS - Davydova S.A. ,; Galeev A.R. ,; Sinyavsky N.I. ,; Eliseeva T.A. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the possibilities of using fitness gadgets in physical education classes in the general education system. Methods and structure of the study. With the help of the Google Forms resource platform, a survey was conducted of 338 physical education teachers representing general educational institutions in the city of Surgut, the results of which with a sufficient degree of reliability allow us to judge the state of the use of fitness gadgets in physical education lessons in the general education system of KHMAO-YUGRA. Results and conclusions. As a result of the survey, a low percentage of readiness of physical education teachers to introduce and use fitness gadgets in the process of teaching the subject "Physical Education" was revealed. Many teachers note the lack of knowledge in the field of information technology and experience in working with them, and also point to the poor development of diagnostic tools for assessing the use of fitness gadgets in educational activities.